x = -3; y = 6; 6y/x = 6(6)/-3 = 36/-3 = -12
E = 24/z or, equivalently, z = 24/E
72
x=y-8 z=x+12
3x + 2 = 82
z = -80
z / 6 = 42 Multiply both sides by 6 to get z = 42 * 6 So z =252
z/6 = -5/12, cross multiply. z*12 =-5*6 z = -30/12 z= -5/2
(z - 8) / 6 = -4 Multiply both sides by 6: (z - 8) = -24 Add 8 to both sides: z = -16
8=(15-z)/68*6=15-z48=15-z33=-zz=-33
6 + z/9 = 9 Therefore, z/9 = 3 3 x 9 = 27 Therefore, z = 27
-12
6+z = 3 z = 3-6 z = -3
1
x = -3; y = 6; 6y/x = 6(6)/-3 = 36/-3 = -12
E = 24/z or, equivalently, z = 24/E
(z - 6)(z - 6)